The higBA-Type Toxin-Antitoxin System in IncC Plasmids Is a Mobilizable Ciprofloxacin-Inducible System - Qi, Qin (mSphere, 2021)
A putative type II toxin-antitoxin (TA) module almost exclusively associated with conjugative IncC plasmids is homologous to the higBA family of TA systems found in chromosomes and plasmids of several species of bacteria. Despite the clinical significance and strong association with high-profile antimicrobial resistance (AMR) genes, the TA system of IncC plasmids remains largely uncharacterized. In this study, we present evidence that IncC plasmids encode a bona fide HigB-like toxin that strongly inhibits bacterial growth and results in cell elongation in Escherichia coli. IncC HigB toxin acts as a ribosome-dependent endoribonuclease that significantly reduces the transcript abundance of a subset of adenine-rich mRNA transcripts. A glycine residue at amino acid position 64 is highly conserved in HigB toxins from different bacterial species, and its replacement with valine (G64V) abolishes the toxicity and the mRNA cleavage activity of the IncC HigB toxin. The IncC plasmid higBA TA system functions as an effective addiction module that maintains plasmid stability in an antibiotic-free environment. This higBA addiction module is the only TA system that we identified in the IncC backbone and appears essential for the stable maintenance of IncC plasmids. We also observed that exposure to subinhibitory concentrations of ciprofloxacin, a DNA-damaging fluoroquinolone antibiotic, results in elevated higBA expression, which raises interesting questions about its regulatory mechanisms. A better understanding of this higBA-type TA module potentially allows for its subversion as part of an AMR eradication strategy. IMPORTANCE Toxin-antitoxin (TA) systems play vital roles in maintaining plasmids in bacteria. Plasmids with incompatibility group C are large plasmids that disseminate via conjugation and carry high-profile antibiotic resistance genes. We present experimental evidence that IncC plasmids carry a TA system that functions as an effective addiction module and maintains plasmid stability in an antibiotic-free environment. The toxin of IncC plasmids acts as an endoribonuclease that targets a subset of mRNA transcripts. Overexpressing the IncC toxin gene strongly inhibits bacterial growth and results in cell elongation in Escherichia coli hosts. We also identify a conserved amino acid residue in the toxin protein that is essential for its toxicity and show that the expression of this TA system is activated by a DNA-damaging antibiotic, ciprofloxacin. This mobile TA system may contribute to managing bacterial stress associated with DNA-damaging antibiotics.